The Possible Antecedents and Consequences of Matching of Food Intake: Examining the Role of Trait Self-Esteem and Interpersonal Closeness - Hirata, Elizabeth; Lodder, Gerine M. A.; Kühnen, Ulrich; Lippke, Sonia; Hermans, Roel C. J. (Frontiers in Psychology, 2015)
Although there is evidence that people tend to match their intake to that of others, less is known about the motives underlying this effect. The current study, therefore, examined the relationship between self-esteem, a specific factor that has been related to the likelihood of social matching. Further, we examined the effects of food matching on interpersonal closeness among eating companions. The sample included 89 female dyads. All dyads had free access to palatable snack food during a 15 minutes interaction. For each dyad the matching score was calculated, as well as both individual’s trait self-esteem scores and interpersonal closeness with their eating partner. The overall degree of matching within dyads was high, replicating the findings of previous research. No relationship, however, was found between trait self-esteem and the degree of matching. Furthermore, there was no effect of matching on perceived interpersonal closeness with or liking of the other person. These results suggest that self-esteem might not be a robust predictor of matching and that matching of food intake may not result in increased perceived interpersonal closeness or liking among eating partners.